Purification and biochemical characterization of a puromycin-sensitive aminopeptidase from black carp muscle. Issue 7 (July 2015) - Li, Si-Wei; Lin, Li-Ping; Chen, Su-Hua; Fu, Meng-Yu; Wu, Guo-Ping
Graphical abstract (A) Changes of potential aminopeptidases activities in black carp muscle during salting from 0 to 12 days. (B) SDS-PAGE. Lane M, molecular weight marker; Lanes 1–5, protein samples from the purification stages of crude extract, 30–70% ammonium sulfate precipitation, DEAE-Sephacel, Phenyl-Sepharose, and Hydroxylapatite. SDS-PAGE and MALDI-TOF mass analysis of aminopeptidase from black carp muscle. (C) MALDI-TOF mass analysis of the purified aminopeptidase.